Bakpau dan Biaya: Mana Metode Harga Pokok Produksi Terbaik? - Khairunnisa Putri; Tiya Nurfauziah; Syarbini Ikhsan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This home industry in determining the cost of production only includes raw material costs, labor costs, and some overhead costs without including other costs. In the withdrawal, it still uses the traditional method and only uses estimates. This study aims to compare the results of the method of calculating the cost of production by home industry and applying two accounting calculation methods, namely the full costing method and variable costing in the Home Industry Mekana Kek in Pontianak. This research is a qualitative research that aims to understand in depth the phenomenon studied through data collection with a direct survey method at the research location through data collection in the form of interviews and observations. The data collected are descriptive and qualitatively analyzed. The results of the study show that the results of the calculation of the cost of production carried out by Home Industry Mekana Kek are relatively low and still do not apply the right method compared to the full costing and variable costing methods. In addition, there is a difference in the calculation of the cost of production of making Mekana Kek Home Industry buns with the full costing method and variable costing. This happens because of the difference in cost charges.